A survey on enhanced power graphs of finite groups - Xuanlong Ma; Andrei Kelarev; Yuqing Lin; Kaishun Wang (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
We survey known results on enhanced power graphs of finite groups. Open problems, questions and suggestions for future work are also included.